2014
DOI: 10.1007/s12032-014-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment of osteosarcoma of the jaw: a single institution experience

Abstract: Osteosarcomas of the jaws are rare mesenchymal tumors frequently diagnosed in the fourth decade of life which account for 6 % of all osteosarcomas. This study evaluated the efficacy on the patients outcome of multimodality treatment consisting of surgery, chemotherapy and radiotherapy. The records of 22 patients affected by jaw osteosarcoma treated with a combination of surgery, poly-chemotherapy and adjuvant radiotherapy in selected cases were reviewed. Response rate, progression-free survival and overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Primary site between mandible and skull/facial bones was another factor that was found not to have a significant effect on survival, which is consistent with several studies. 15,22,24,45,60 However, while significance was not found for primary site, slight differences in survival were found, with JOS in the mandible having increased OS and DSS median survival compared with JOS in the skull/facial bones. This may be because of the complex anatomy of the maxilla, which makes it technically difficult to achieve clear margins.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Primary site between mandible and skull/facial bones was another factor that was found not to have a significant effect on survival, which is consistent with several studies. 15,22,24,45,60 However, while significance was not found for primary site, slight differences in survival were found, with JOS in the mandible having increased OS and DSS median survival compared with JOS in the skull/facial bones. This may be because of the complex anatomy of the maxilla, which makes it technically difficult to achieve clear margins.…”
Section: Discussionmentioning
confidence: 93%
“…12,17 In addition, the role of radiation therapy for the treatment of JOS is unclear because some studies have reported significant improvement in survival with radiation therapy in patients with positive or uncertain margins, while others report no significant improvement for patients with positive or negative margins. 1,3,11,15,[19][20][21][22][23][24] A large population-based study of JOS could help clarify the roles of multimodal therapy in JOS treatment. While there are several single and multicenter studies reported, population data are scarce and controversial.…”
mentioning
confidence: 99%
“…According to Ferrari et al [60], a multimodal approach consisting of radical surgery and CTx, with or without RTx, favorably compares with previous reports, achieving 5-year OS and DFS rates of 77 and 73%, respectively. In line with retrospective reviews stressing the prognostic importance of CTx-induced necrosis for local control [11,25] also in this study, the rate of necrosis was a statistically signiicant factor, with poor prognosis correlating with ≤50% necrosis.…”
Section: Medical Treatmentmentioning
confidence: 59%
“…The CT scan allows a beter assessment of the bone involvement and extension (beter hard tissue deinition), whereas the MR imaging aims at deining with considerable accuracy the soft tissue involvement [60].…”
Section: Surgerymentioning
confidence: 99%
“…Osteosarcoma of the jaw is rare, accounting for ~1% of all head and neck malignancies (9). The disease has a moderate male predilection, with a peak in incidence in the second to third decades of life (10).…”
Section: Discussionmentioning
confidence: 99%